(untitled) (Ustozlar uchun, 2025)
This article investigates the effect of technology on English language learning in contemporary educational settings. It examines how technological tools support the development of listening, speaking, reading, and writing skills, while also enhancing learner motivation and autonomy. The study discusses the role of digital resources in providing authentic language exposure and personalized learning opportunities. Additionally, challenges such as unequal access to technology, digital distraction, and the necessity of teacher guidance are analyzed. The article concludes that technology, when integrated effectively with traditional teaching methods, significantly improves the quality and effectiveness of English language learning.